The Beauharnois Scandal : A Story of Canadian Entrepreneurship and Politics - Regehr, T. D. (Book collections on Project MUSE., 1990)
T.D. Regehr has drawn extensively from archival material to tell the story of Beauharnois in all its facets: entrepreneurial, financial, administrative, technological, and political. He gives an intriguing account of one of the less glorious episodes in Canadian corporate history.